MODEL PEMBELAJARAN MATEMATIKA BERBASIS MEDIA INTERAKTIF PADA PONDOK PESANTREN AL-JAUHAREN JAMBI SEBERANG: Media, Learning, Mathematics, adobe flash CS5 - -, Riswan (LP2M Universitas Nurdin Hamzah, 2017)
Research was conducted at boarding AL-Jauharen Jambi Opposite to the process of teaching mathematics. This study aims to look at how the process of teaching the teachers and what obstacles encountered in the learning process. Mathematics teaching process is still done manually, the teacher is very dominant, the students have been hearing what the teacher explained. This method menghasil student learning outcomes were not significant, the math is still considered a difficult subject. Need to develop a mathematical model of a more interactive learning based on ICT, to improve student learning outcomes. Allows teachers and students in the learning process. To attract the attention and interest of student learning, to focus on understanding the material presented by the teacher. Waterfall methodology used to develop this model, by the way from the field to know directly the problems facing the MTS Pondok Pesantren Al-Jauharen Seberang Jambi. The results of this study resulted in an ICT-based interactive learning model designed using Adobe Flash CS5.